Solder joint stability study of wire-based interconnection compared to ribbon interconnection. (September 2017) - Walter, Johann; Rendler, Li C.; Ebert, Christian; Kraft, Achim; Eitner, Ulrich
Abstract: For the comparative study with focus on mechanical long-term stability, we perform a temperature cycle (TC) test-to-failure for 1250 cycles according to IEC 61215 with laminated solar cell strings. The strings were produced with Multi Busbar (MBB) solar cells interconnected by wires and with solar cells with 3 busbars (3BB) interconnected by ribbons. One module sample comprises two electrically isolated 3-cell strings, one for each technology. The 3BB string displays a power loss of more than 5 % after 850 cycles, while the MBB string only exceeds 5% loss after 1250 cycles. After TC 1250 the 3BB string shows a degradation of -8.2 % in FF and -8.0 % in power, while the MBB string shows a degradation of -6.2 % in FF and of -5.3 % in power. In the second comprehensive comparative study we use for each interconnection technology 15 cells for isothermal storage (up to 130 °C, 42.8h) and 10 modules for TC (up to 400 cycles). Each reliability analysis includes IV and EL characterization as well as adhesion force measurements and microsection analysis. After TC 400 the MBB interconnection shows less than 1 % degradation in efficiency compared to 4-5 % degradation for 3BB ribbon interconnection in a common module setup. The cells and modules show that most of the electrical contacts are still intact with respect to the EL image after 42.8 h isothermal storage and TC 400, although the average peel forces degraded from about 2 N/mm to less than 0.5 N/mm. Both studies indicate a superior mechanical long-term stability for Multi Busbar technology compared to ribbon interconnection.